2013
DOI: 10.1111/1744-7941.12003
|View full text |Cite
|
Sign up to set email alerts
|

Business expatriates' cross‐cultural adaptation and their job performance

Abstract: While a positive relationship between the cross-cultural adaptation and job performance of business expatriates is widely assumed and intuitively plausible, empirical studies do not consistently confirm this relationship. The current quantitative study investigated expatriates sent to and from China, two hitherto neglected but increasingly important groups. The sample of more than 800 participants is considerably larger than in previous studies of other types of expatriates. The study, in the Chinabased contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
0
20
0
4
Order By: Relevance
“…Our empirical research results indicate particular problems peculiar to expatriation to China (Shi and Franklin 2014). China is one of the most important countries as both a low-cost manufacturing site and an emerging market for Japanese MNCs.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our empirical research results indicate particular problems peculiar to expatriation to China (Shi and Franklin 2014). China is one of the most important countries as both a low-cost manufacturing site and an emerging market for Japanese MNCs.…”
Section: Discussionmentioning
confidence: 85%
“…Whatever the reasons for the expatriation, it is clear that none of them will be achieved unless the expatriate is able to adjust to their new environment and to perform well at work (Shi and Franklin ). Any failure of expatriation will bring a substantial loss, directly or indirectly, to the organization (Black et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Lauring and Selmer (2010) postulated that married expatriates are more successful than singles in securing high chances of assignment success. A previous research by Shi and Franklin (2013) presented that if the spouse adjusts favourably, it will assist expatriates in focusing on their job. Spouses can search for information about a general environment in the host country to improve expatriates' general adjustment (Kraimer et al 2001).…”
Section: Host Country National Supportmentioning
confidence: 99%
“…The relationship between job performance and cultural adjustment has been studied by several researchers (e.g., Shi & Franklin, 2014). Wang and Tran (2012) found that an expatriate's interaction and work adjustment have significant impacts on job performance.…”
Section: Mediating Role Of Cultural Adjustmentmentioning
confidence: 99%